2000
DOI: 10.1097/00000658-200006000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes After Ileal Pouch-Anal Anastomosis for Chronic Ulcerative Colitis

Abstract: ObjectiveTo assess long-term outcomes after ileal pouch-anal anastomosis (IPAA) for chronic ulcerative colitis (CUC) with specific emphasis on patient sex, childbirth, and age. Summary Background DataChildbirth and the process of aging affect pelvic floor and anal sphincter function independently. Early function after IPAA is good for most patients. Nonetheless, there are concerns about the impact of the aging process as well as pregnancy on long-term functional outcomes after IPAA. MethodsFunctional outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
188
3
8

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(212 citation statements)
references
References 23 publications
13
188
3
8
Order By: Relevance
“…Pouch failure occurred in 1 patient (1.2%), who was then converted to permanent ileostomy. The majority of studies have reported that pouchitis is the most frequent long-term complication of the IPAA, ranging from 12% to 50% (18,19). Pouch-vaginal fistula has been reported as a major complication in women undergoing IPAA, of which the incidence ranges from 3.3%-12% (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Pouch failure occurred in 1 patient (1.2%), who was then converted to permanent ileostomy. The majority of studies have reported that pouchitis is the most frequent long-term complication of the IPAA, ranging from 12% to 50% (18,19). Pouch-vaginal fistula has been reported as a major complication in women undergoing IPAA, of which the incidence ranges from 3.3%-12% (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…No obstante la ausencia aparente de complicaciones sépticas de la anastomosis en ese tiempo quirúrgico, tres pacientes presentan complicaciones de la anastomosis luego de cierre de la ileostomía (una fístula a la vagina y dos fístula perineales complejas entre 2 y 8 meses). Los tres pacientes tenían una reservoriografía normal, lo que es consistente con otras series de mayor volumen 1,5,6,[10][11][12] . Los resultados funcionales de esta serie se han cotejado según el puntaje de Öresland, score modifi cado por el mismo autor en publicaciones posteriores 3,13 .…”
Section: Discussionunclassified
“…Por otra parte, en seguimientos por sobre 15 años se puede constatar un deterioro de la función esfi nteriana en algunos pacientes por efecto de la edad 13 . Al igual que en series numerosas, el 70% de los pacientes presenta al menos una evacuación nocturna, cifra que en la literatura fl uctúa entre 24% y 76% [10][11][12][13][14] . Es llamativa la ausencia de difi cultad para la evacuación (disquezia que se defi ne como más de 15 minutos en el baño al menos 1 vez a la semana) en esta serie.…”
Section: Discussionunclassified
See 2 more Smart Citations